2021
DOI: 10.1002/brb3.2386
|View full text |Cite
|
Sign up to set email alerts
|

Lie to my face: An electromyography approach to the study of deceptive behavior

Abstract: Background: Deception is present in all walks of life, from social interactions to matters of homeland security. Nevertheless, reliable indicators of deceptive behavior in reallife scenarios remain elusive.Methods: By integrating electrophysiological and communicative approaches, we demonstrate a new and objective detection approach to identify participant-specific indicators of deceptive behavior in an interactive scenario of a two-person deception task. We recorded participants' facial muscle activity using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The analysis we presented in this paper suggests that the AU-based approach has an inherently limited ability to reliably compare between different sessions and individuals. Reservations about the validity of CV in studying facial expressions are recognized both among computer vision specialists [31] and among investigators studying facial expressions from psychological and neurological perspectives [17,32]. Accordingly, better algorithms and data sets PLOS ONE continue to be developed [33].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis we presented in this paper suggests that the AU-based approach has an inherently limited ability to reliably compare between different sessions and individuals. Reservations about the validity of CV in studying facial expressions are recognized both among computer vision specialists [31] and among investigators studying facial expressions from psychological and neurological perspectives [17,32]. Accordingly, better algorithms and data sets PLOS ONE continue to be developed [33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, combining the EMG signals with support vector machine classification and unsupervised peak-density clustering, we recently showed that deceptive behavior and expressions of subjects that face each other, i.e. involved in direct interaction instead of in an artificial laboratory setup, is different than in traditional setups [40].…”
Section: Applicationsmentioning
confidence: 99%
“…Unorthodox lie detection studies analyze video and audio 6 (including facial expressions 7,8 , pupil reaction 9, and delays between question and answer 10) , electromyography (EMG) 11 , electroencephalogram (EEG) 12 , magnetic resonance tomography (MRT) 13,14 , or writing pattern (keystroke dynamics) 15 in addition to or instead of classical polygraph data. Some of these studies even get a chance to pilot in the new elds, such as the iBorderCtrl lie detector pilot in EU airports 16,17 or the VeriPol deception detection pilot by Spanish police on written insurance claims 18,19 .…”
Section: Mainmentioning
confidence: 99%